Personality theories a global view - Shiraev, Eric 1960- (SAGE, 2017)
"Personality Theories: A Global View by leading scholar Eric Shiraev takes a dynamic, integrated, and cross-cultural approach to the study of personality. The text is organized around three general questions: Where did personality theories come from? How did the theorists study facts? How do we apply personality theories now? These questions provide a consistent focus on social context, interdisciplinary science, and applications. Going beyond traditional research from the Western tradition, the book also covers theories and studies rooted in the experiences of other countries and cultures." -- Back cover of book.